5(4+8x)=-4x-4(x-5)

Simple and best practice solution for 5(4+8x)=-4x-4(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4+8x)=-4x-4(x-5) equation:


Simplifying
5(4 + 8x) = -4x + -4(x + -5)
(4 * 5 + 8x * 5) = -4x + -4(x + -5)
(20 + 40x) = -4x + -4(x + -5)

Reorder the terms:
20 + 40x = -4x + -4(-5 + x)
20 + 40x = -4x + (-5 * -4 + x * -4)
20 + 40x = -4x + (20 + -4x)

Reorder the terms:
20 + 40x = 20 + -4x + -4x

Combine like terms: -4x + -4x = -8x
20 + 40x = 20 + -8x

Add '-20' to each side of the equation.
20 + -20 + 40x = 20 + -20 + -8x

Combine like terms: 20 + -20 = 0
0 + 40x = 20 + -20 + -8x
40x = 20 + -20 + -8x

Combine like terms: 20 + -20 = 0
40x = 0 + -8x
40x = -8x

Solving
40x = -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
40x + 8x = -8x + 8x

Combine like terms: 40x + 8x = 48x
48x = -8x + 8x

Combine like terms: -8x + 8x = 0
48x = 0

Divide each side by '48'.
x = 0

Simplifying
x = 0

See similar equations:

| -5(-4x-5)=-7+8(x+1) | | 6+4x-2y=0 | | 4y-13=-2-3y | | -74=-2(6x+4)+6(1-2x) | | 8y-21=12y-29 | | 3x^2-53x=-56 | | 6--3x=5x-10x+18 | | 3(3.41)+2(0.99)+4h=19.29 | | t+18.1=23.1x | | .037x+.079(.01-x)=.065(.01) | | 4(2x-8)=8(4x+2) | | 7(-5r-5)-8=4(1+5r)-8r | | 5y*3y=24 | | 5x+3=7x-27 | | 10x+3(5)=20 | | x/3-3=5/6 | | 5=5-7n-5n | | X-4+7=0 | | -7(-3+a)=-a+5(-4a+7) | | 3(2a-5)+1=4 | | -2(8n-1)-7(-n+5)=1-3n+2-3n | | 1.25x+x^2= | | y=-0.2x^2-32x+2 | | 4x+6x-2(x-2)=3(4x+7) | | x=10+.25X | | lnx+2(lnx^2)=6 | | lnx-2(lnx^2)=6 | | B-9+6b=40 | | 380=40t+60t-120 | | 2x+-5x+(8x+6x)=5 | | 2x-5x+(8x+6x)=x | | a=p+1fora |

Equations solver categories